Parliament And Representation In Ghana - Aggrey-Darko, E. (O’mens Graphix, Accra, 2007)
As a political principle, representation is a relationship through which an individual or group stands for, or acts on behalf of a larger body of people. Representation sometimes generates political controversy. Even absolute monarchs of the 16th and 17th centuries in Europe to a very large extent were expected to rule by seeking the advice of the major landed interest, the clergy and others (Heywood 2002:224). The attempt to undermine this principle of representation resulted in the 17th century Civil War in England. The controversy surrounding representation has somehow been resolved through the widespread acceptance of the principle of political equality which emphasises one person, one vote plus real choices